PENINGKATAN KEROHANIAN PELAJAR SEKOLAH TEOLOGI: STUDI FORMAT SPIRITUAL DI MALAYSIA EVANGELICAL SEMINARY BELAGA - Angku Jalong (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2020)
Abstract: Spirituality is highly emphasized for someone who wants to dive into the field of theological schools, especially in Malaysia Evangelical Seminary Belaga highlights the three main pillars for the existing Theology schools, which is to want those schools to be identical to the three pillars that are standard. such as; High academic, high discipline and high spirituality. The question that arises in the following question: How important is the Spiritual Development of Theological Students? How is the Bible's Guide to Improving Spirituality? What is the spirituality of a Condition to Meet the Degree Standards of Theology School Students? The answer is (1) Learning strategies to increase spirituality in METS Belaga schools will definitely continue to be realized with the involvement and cooperation of the center and METS itself with full submission to the leadership of the Holy Spirit. (2) The guide to improving the quality of spirituality based on the Bible is that teachers should give comprehensive attention so that students can assess and track the extent of their spiritual development. (3) By giving systematic instruction to the students alone they can understand this life which must change constantly in this life for the glory of His name. Abstrak: Kerohanian sangat ditekankan bagi seseorang yang mahu menerjunkan diri dalam bidang sekolah teologi, khususnya di Malaysia Evangelical Seminary Belaga mengetengahkan tiga pilar utama untuk sekolah-sekolah Teologia sedia ada, iaitu mahu sekolah-sekolah tersebut identik dengan tiga pilar yang menjadi piawan(standard) seperti; Academis yang tinggi, disiplin yang tinggi dan kerohanian yang tinggi. Persoalan yang muncul dalam pertanyaan berikut: Bagaimanakah pentingnya Membangun Spiritual Pelajar Teologi? Bagaimanakah panduan Meningkat Mutu Kerohanian  berdasarkan Alkitab? Bagaimanakah kerohanian satu Syarat untuk Memenuhi Standar Gelar Pelajar Sekolah Teologi? Jawaban adalah (1) Strategi learning untuk meningkatkan kerohanian di sekolah METS Belaga pasti akan terus terealisasi dengan penglibatan dan kerjasama pihak pusat dan METS itu sendiri dengan penuh penyerahan kepada pimpinan Roh Kudus. (2) Panduan meningkat mutu kerohanian  berdasarkan Alkitab adalah para guru harus memberi perhatian yang menyeluruh agar para pelajar dapat menilai dan mengesan sejauh mana keadaan perkembangan kerohanian mereka. (3) Dengan memberi pengajaran yang sistematis kepada para pelajar saja mereka dapat mengerti kehidupan ini yang harus berubah terus menerus dalam hidup ini bagi kemuliaan nama-Nya.